Evidence of thermohaline staircase in the Cretan Sea (Eastern Mediterranean Sea) - Velaoras, Dimitris; Kioroglou, Sotiris; Bourma, Evi; Ballas, Dionysios; Zervakis, Vassilis (Frontiers in Marine Science, 2025)
This work presents evidence of double diffusive convection (DDC) in the form of salt fingers (SF) forming a thermohaline staircase in the Cretan Sea (South Aegean Sea). The phenomenon was identified at the eastern edge of the Cretan Sea in March 2023 but had vanished by September 2023. To estimate vertical diffusivities and fluxes, four DDC models were applied to the hydrographic data. The vulnerability of the staircase appears to be related to weak, downward, salt finger–induced density fluxes, possibly caused by tilting of the salt fingers due to prevailing strong horizontal shears. Two of the four model implementations showed closer agreement with predictions from a previous staircase study in the area. Analysis of the density ratio and Turner angle from individual cruises demonstrated the widespread susceptibility of the Cretan Sea water column to such phenomena. Specifically, cruise data from 2016 to 2023, covering the layer between the intermediate salinity maximum (Levantine Intermediate Water) and the deep salinity minimum (Transitional Mediterranean Water), showed that 71%–85% of Turner angle values lie in the salt fingering zone. Thermohaline staircases in the Cretan Sea play a significant role in shaping the physical and biochemical processes of the basin by transporting salt and density toward deeper layers while uplifting nutrients. Although small scale, the phenomenon can significantly influence the evolution of the water column and large-scale climatic processes, such as vertical heat and salt transport and overturning circulation in deep basins.